Strengthening Emergency Medical Services Under Vision 2030: The Expanding Role Of Paramedics In Saudi Arabia (The Review of Diabetic Studies, 2025)
Emergency Medical Services (EMS) are undergoing a rapid transformation in Saudi Arabia under the national Vision 2030 framework, which seeks to enhance healthcare quality, accessibility, and responsiveness. Paramedics have emerged as key agents in achieving these goals through the delivery of advanced prehospital care, technological integration, and patient-centered service models. This review explores the expanding role of paramedics in strengthening EMS within the Saudi context. Drawing on evidence from 2016 to 2025, it examines developments in paramedic education, professional regulation, and digital transformation—highlighting innovations such as smart ambulance systems, telemedicine, and AI-assisted dispatch networks. The findings demonstrate that paramedics are pivotal in reducing response times, improving survival rates, and bridging the gap between on-site emergencies and hospital-based care. Despite significant progress, challenges remain in standardizing training, ensuring gender inclusion, and establishing unified national accreditation systems. The review concludes by proposing a strategic framework that aligns paramedic workforce development and technological advancement with Vision 2030 objectives for sustainable, high-quality emergency healthcare.